2017
DOI: 10.1055/s-0043-118797
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of outcomes of carpal tunnel release for carpal tunnel syndrome in patients diagnosed with and without electrophysiological studies

Abstract: Records were analysed from the institutional database, including 943 patients (1089 hands) with CTS who were operated on in the authors' department over a period of four years (2012 to 2015). The diagnosis of CTS was made solely on the basis of clinical findings in 551 patients (58 %); 392 patients (42 %) also had electrodiagnostic tests performed, for various reasons. Patients were followed-up at 1 and 6 months with assessments that included the Levine scores, filament tests, grip and pinch strength. No signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“… 15 16) There are abundant reports on grip strength recovery patterns following CTR, and most researchers have suggested that patients usually achieved total grip strength recovery 3 to 6 months postoperatively ( Table 1 ). 2 17 18 19 20 21 22 23 24 25 26 27) Some researchers reported rapid grip strength recovery in 4 to 6 weeks postoperatively. 2 17 19 23) …”
Section: Grip Strength In Carpal Tunnel Syndromementioning
confidence: 99%
“… 15 16) There are abundant reports on grip strength recovery patterns following CTR, and most researchers have suggested that patients usually achieved total grip strength recovery 3 to 6 months postoperatively ( Table 1 ). 2 17 18 19 20 21 22 23 24 25 26 27) Some researchers reported rapid grip strength recovery in 4 to 6 weeks postoperatively. 2 17 19 23) …”
Section: Grip Strength In Carpal Tunnel Syndromementioning
confidence: 99%